Carol's Father - unknown:::Creator::::::::::::
Wilbur Henning (father of Carol) holding golf clubs and standing in front of his Studebaker and home at 235 South 16th Street in San Jose, California. Colorized. Hard copy (25cm by 17,5cm) found in one of Carol's scrapbooks.